Migration from Subversion to Git Version Control System - Varshney, Monika; Shrivastava, Azad Kumar; Aggarwal, Alok; Kumar, Adarsh (International Journal of Computer Sciences and Engineering, 2018)
In recent years, software development in software industries is getting a transition from centralized version control systems (CVCSs) like subversion, mercurial, perforce, CVS etc. to decentralized version control systems (DVCSs) like Git due to a number of reasons like time, space, branching, merging, offline commits & builds and repository etc. Both centralized VCSs and distributed VCSs have gone through ample investigations in recent past but individually from the software developer’s point of view in a large commercial software industry. There has been a little focus on the transition across Git having a share of more than three-fourth of total VCS, and Subversion having a share of 13.5%. In this work transition process from Subversion VCS to Git VCS has been investigated.